Ultimate government control structures and firm value: Evidence from Chinese listed companies - Kun Wang; Xing Xiao (China Journal of Accounting Research, 2009)
We show that 70% of Chinese listed companies are ultimately controlled by government agencies, thereby indicating that state ownership remains widespread in China's stock markets. Three questions are considered that are related to government control structures and their impact on firm value: (1) how do government agencies maintain their control of listed companies; (2) what are the impacts of different government control structures on firm value; and (3) are these impacts different in local government and central government-controlled firms? We find that the Chinese government controls listed companies directly or indirectly through solely state-owned enterprises (SSOEs). Taking into account the trade-off between political and agency costs, we show that firm value increases when some control rights are decentralized from the government to state-owned enterprises (SOEs). Moreover, decentralization improves significantly the performance of local government- controlled, but not central government-controlled firms.
Keywords: G32; G34; G15; 650; Government control structures; Firm value; Agency costs; Political costs; Decentralization